(untitled) (Research, Society and Development, 2021)
The objective of this study is to analyze how the use of hormonal contraceptive methods and intrauterine devices (IUD) can influence the use of barrier contraceptive methods, assessing whether there is an association with increased prevalence of sexually transmitted infections (STIs) in young women (aged 20 to 30 years). Were analyzed medical records of the years 2018 and 2019 of the Specialized Center for Infectious and Parasitic Diseases (CEDIP) in Cascavel-PR, of women diagnosed with sexually transmitted infections that fit the specific age range. Most women diagnosed with STI use hormonal contraceptive or intrauterine device (58%). Of these women, only 45% make concomitant use of some barrier method and of these 59% use it irregularly. Thus, it was found that 81% of women with STIs do not use barrier condoms or use them incorrectly. Through inferential analyzes of the data obtained, it was possible to establish a hypothesis with a statistically significant value, that is, p<0.05, that women using barrier contraceptives contract less STIs than women who choose other contraceptive methods, such as hormonal contraceptives and IUD. This result supports the project’s hypothesis that only the use of hormonal contraceptives or IUD does not protect against the spread of STIs.